2004
DOI: 10.1037/0002-9432.74.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Measuring child maltreatment: A comparison of prospective parent reports and retrospective adolescent reports.

Abstract: Using Lehigh Longitudinal Study data (N = 457), the authors compare prospective parent self-reports and retrospective adolescent reports of early childhood physical abuse, exploring their correspondence, predictive equivalence, and outcomes associated with conflicting reports. Correspondence between prospective and retrospective reports of child maltreatment was moderate (Phi = 0.27). Concurrence rates were similar for males and females. Analyses of the relative predictive capacity of prospective and retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 24 publications
6
103
2
2
Order By: Relevance
“…Perhaps most troubling is the abundance of studies that use cross-sectional designs and retrospective measures of child maltreatment, absent validation against prospective measures [4,7]. The use of cross-sectional designs leads to ambiguity in causal effects; retrospective measurement is problematic because assessment depends on accurate recall of distant childhood events, which are subject to distortion and/or selectively recalled.…”
Section: Protection and Resiliencementioning
confidence: 94%
See 2 more Smart Citations
“…Perhaps most troubling is the abundance of studies that use cross-sectional designs and retrospective measures of child maltreatment, absent validation against prospective measures [4,7]. The use of cross-sectional designs leads to ambiguity in causal effects; retrospective measurement is problematic because assessment depends on accurate recall of distant childhood events, which are subject to distortion and/or selectively recalled.…”
Section: Protection and Resiliencementioning
confidence: 94%
“…In the child maltreatment literature, more universal methodological shortcomings exist [7,[17][18][19], which further undermine the strength of existing knowledge on resilience for abused children. Perhaps most troubling is the abundance of studies that use cross-sectional designs and retrospective measures of child maltreatment, absent validation against prospective measures [4,7].…”
Section: Protection and Resiliencementioning
confidence: 94%
See 1 more Smart Citation
“…However, recent work has suggested that they are more reliable than previously thought (Tajima, Herrenkohl, Huang, & Whitney, 2004). The second limitation of the study is the self-report of childhood abuse history by participants especially with mental illness, which might be liable to recall bias even though a review by Brewin, Andrews, and Gotlib (1993) has indicated that the recall of childhood abuse by adults has been relatively accurate.…”
Section: Childhood Abuse and Severe Mental Illnessmentioning
confidence: 95%
“…Additionally, prospective measures have the benefit of recency, reducing the chances that the events are forgotten or distorted by later experiences (Tajima, Herrenkohl, Huang, & Whitney, 2004). However, recent events may also be underreported if the issues are particularly sensitive, such as childhood victimization, where the child may fear that disclosure will lead to a negative outcome for them (e.g., retaliation from their abuser, removal from their home, etc.…”
Section: Sampling Limitationsmentioning
confidence: 99%